Physiological periostitis in a 2.5-month-old baby - Haıcıoğlu, Oya; Aşık-Akman, Sezin; Yaprak, Işın; Astarcıoğlu, Görkem; İmamoğlu, Tuna and Reisoğlu, Ali (The Turkish Journal of Pediatrics, 2009)
Periosteal reaction has different etiologies in early infancy. Physiological periostitis is a well-documented X-ray finding seen in both preterm and term babies aged between 1-6 months and can easily be misdiagnosed as child abuse or pathological periostitis. Here, we present a 2.5-month-old infant admitted with a history of fever, swollen right upper arm after vaccination and X-rays findings revealing periosteal reactions on both sides of the humeri, radii, tibiae and femora. Initial diagnosis was child abuse or congenital syphilis. Due to the normal physical findings and normal serological-biochemical data, physiological periostitis was diagnosed. Physiological periostitis should also be considered in patients with periosteal reactions of the long bones in infants aged between 1-6 months.